Cutting Edge Research? Realistic Expectations of Priorities, Scope and Engagement; Comment on “‘We’re Not Providing the Best Care If We Are Not on the Cutting Edge of Research’: A Research Impact Evaluation at a Regional Australian Hospital and Health Service” - Siân Williams; Genevie Fernandes (International Journal of Health Policy and Management, 2023)
While research is linked with informed decision-making and improved healthcare delivery and patient outcomes, the process of generating and translating research evidence in practice and capturing its impact can often be challenging. Based on document and database reviews and interviews in a regional Australian health system, Brown et al discuss the challenges of assessing the impact of research investments over a ten-year period. This commentary explores three inter-related lessons from this article for developing and sustaining a research culture and supporting translation in a health system: (i) achieving a shared definition and expectation of research; (ii) the importance of stakeholder engagement particularly for research prioritisation; and (iii) enabling research across a system. In doing so, it highlights the role and value of engaging knowledge generators and end-users from clinical, management and community domains not only in research development but most importantly in research prioritisation.